E-034 Optimal management approach for treating anterior communicating artery aneurysm. (22nd July 2019) - Sweid, A; Herial, N; Tjoumakaris, S; Rahm, S; Andrews, C; Gooch, M; Rosenwasser, R; Jabbour, P
Abstract : Introduction: Coiling has been the first line armamentarium for treating intracranial aneurysms, especially ruptured ones. Coiling has a relatively high recurrence rate as compared to clipping which leads to increased costs and procedural risks. Purpose: We aimed to determine complication rates, occlusion outcomes, functional status, and mortality of Anterior communicating artery (ACOM) aneurysms following coiling. We also determined re-treatment rate and compared occlusion outcomes between recoiling and clipping of recurrences. We also assessed factors predictive of aneurysms recurrence. Materials and methods: We performed a retrospective cohort study of consecutive patients with ACOM aneurysms. Results: 516 ACOM aneurysms were included (Av age 55.5 years, 54.3% female). 78% (401) presented as ruptured aneurysms, 55.6% presented with a high-grade H&H. The average aneurysm size was 5.8 mm(SD=2.8). 93%(478) were treated with coiling as stand-alone divided into primary coiling 86%(412), balloon-assisted coiling 12%(57), and stent-assisted coiling 2%(9). While 7%(37) were treated with coiling in addition to clipping, coiling was placed to secure the dome, and then the aneurysm was clipped during the same hospital stay in acute settings. At the end of the procedure, > 95% occlusion was achieved in 90.9% of the cases. The average length of hospital stay was 15.8days, and the mortality rate was 7.2%. There was a significant six folds higher aneurysm recurrence in the coiled group reaching 17.3%(78) while in the clipped/coiled group the recurrence rate was 2.9%(1) (p=0.026). Of all patients with recurrence (n=79), 28 were treated with clipping, 22 with coiling, 16 with coiling followed by clipping due to recurrence, and 13 patients were not re-treated. Out of the whole 38 patients who received coiling at least once, 34 needed recoiling once, 3 required recoiling twice, and 1 patient required recoiling four times. Approximately 76% of coiled patients(n=29) showed recurrence, while none of the clipped patients showed recurrence(p<0.01). There was no significant difference in the proportion of complications between the two groups (25% vs.18%, p=0.56). Complete occlusion was achieved in 65%(n=52) on latest follow up. All patients who were clipped showed complete occlusion, while 32% of the coiled patients showed complete occlusion(p<0.01). RRS class II was seen in 18.9%(n=15), class IIIa in 6%(n=5), and class IIIb in 2.5%(n=2). There was no significant difference in the mean mRS score between the both groups(p=0.11). The average duration of follow up following retreatment was 10 months(95%CI:4–15). Most patients had an mRS score< 2 (n=60). Variables that are significantly associated with aneurysm recurrence are increased aneurysm size and ruptured presentation. Conclusion: The recurrence rate of coiled aneurysms compared to clipping was associated with 6 folds higher rate of recurrence. Clipping of a recurred ACOM aneurysms achieves higher occlusion outcomes, lower recurrence rate, and comparable risk of complication and functional outcome compared to coiling. Increasing aneurysm size and ruptured status was a significant predictor of aneurysm recurrence. Disclosures: A. Sweid: None. N. Herial: None. S. Tjoumakaris: None. S. Rahm: None. C. Andrews: None. M. Gooch: None. R. Rosenwasser: None. P. Jabbour: None.